Semi-selective culture medium for Xanthomonas axonopodis pv. malvacearum detection in cotton seeds (Gossypium hirsutum L.) - Dezordi, Cleci; Maringoni, Antonio Carlos [UNESP]; Menten, José Otavio Machado; Camara, Renata Cassia [UNESP] (Science Alert, 2009)
The cotton disease known as angular leaf spot, caused by Xanthomonas axonopodis pv. malvacearum (Xam) has been causing cotton losses in several producing regions around the world. Xam is transmitted by seeds, which may be infected both externally and internally. Infected seeds constitute the main long-distance dissemination mode of the pathogen. In view of this, the use of healthy seeds is a must. To accomplish that, detection methodologies for the bacteria must be developed be used in seed health analysis laboratories. This study aimed to develop a semi-selective medium for Xam detection in cotton seeds. The semi-selective culture medium was named MSSXAN and it was consisted of peptone (5.0 g), beef extract (3 g), sucrose (5 g), soluble starch (10 g), agar (15 g), CaCl 2 (0.25 g), Tween 80 (10 mL), distilled water (1,000 mL), crystal violet solution at 1% (150 μL), cephalexin (50 mg 1*), methyl thyophanate (10 mg*) and chlorothalonil (10 mg*) - *added after culture medium autoclaving. This MSSXAN medium shows low repressiveness to Xam and it be used for isolation of this bacteria in cotton seeds health analysis. © 2009 Academic Journals Inc.
Keywords: Angular spot; Bacterium; Malvaceae; Phytopathogen; Seed pathology; Bacteria (microorganisms); Gossypium hirsutum; Magnoliophyta; Xanthomonas axonopodis; Xanthomonas axonopodis pv. malvacearum